Natural Antidiabetic of Tunjuk Langit (Helminthostachys zeylanica) Rhizome Extracts - Fania E. Ridhasya; Hilwan Y. Teruna; Rudi Hendra; Muhammad Almurdani (Pharmacology and Clinical Pharmacy Research)
The use of medicinal plants in treating diabetes mellitus is increasing in Indonesia. Plenty of plants from different regions may have anti-diabetic effect, including Helminthostachys zeylanica. This plant is commonly used as a traditional medicine to treat inflammation, cough, dysentery, and malaria in Talang Mamak tribe, Indragiri Hulu, Riau, however in China it is used to treat diabetic. Thus, we examined whether the extract of H. zeylanica originated from Riau have potential antidiabetic activity. We assessed the α-glucosidase inhibitory activity of the extract of H. zeylanica rhizome. The results showed the antidiabetic values of n-hexane, dichloromethane (DCM), ethyl acetate (EtOAc), methanol (MetOH), and ethanol (EtOH) extracts were 380.88 ± 0.09; 190.76 ± 0.22; 61.18 ± 0.59; 47.86 ± 0.06; and 60.78± 0.02, respectively. Acarbose were used as standard with antioxidant values of 19.73± 0.07. It can be concluded that the methanol extract is potential to be proposed as antidiabetic.